ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN BAHASA INDONESIA GUNA MENINGKATKAN KEMAMPUAN MEMBACA SISWA SD - Adienda Sepniria Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Indonesian language lessons in elementary school are often considered boring lessons because they seem to only record material and rarely practice it. This research discusses Indonesian language learning media used in elementary schools to help children develop reading skills. This research can be seen from the results of data analysis from several journals. This research uses qualitative research with a literature study method using secondary data originating from 10 journals that have been analyzed previously. The analysis has been carried out through several stages in reviewing previous research, including: 1) Sorting out relevant research; 2) Collect data and information for review; 3) Determine the state of the art of the research that has been analyzed; 4) Develop the results of information analysis and combine them into a conclusion. The results of this research can be concluded that the existence of learning media is very important in improving reading skills, especially at the elementary school level. It is necessary to utilize Indonesian language learning media to achieve the learning objectives desired by the teacher. And based on the results of the analysis in this research, it is hoped that students will have good reading skills through Indonesian language learning media.